Geodynamics of the Broad Triangle Area (active seismic zone) in Asia: Stress field modeling. (February 2020) - Duan, Shangchang; Hou, Guiting; Yang, Lihui
Highlights: A first numerical model was established for the mechanism of the BTA. The spherical shell model was established to avoid system errors. Abstract: The Broad Triangle Area (BTA) is a significant active seismic zone located mainly in East Asia. The Pamir-Baikal tectonic belt, North-South tectonic belt and Himalayan tectonic belt compose the three boundaries of the BTA. Previous studies suggested that the geodynamics of the BTA may be related to coupling between the Indian and Eurasian plates, yet quantitative analysis is lacking. In this study, we use the elastic finite element method in the ANSYS software to establish a spherical shell model and analyze the stress field of the model. We obtain a best-fit model that matches the geological evidence and seismicity by considering the real geological background; a series of models with different initial settings are also discussed to analyze the boundary influence on the different models. Our modeling results indicate that the India-Eurasia collision, the stable Siberia craton and the blocking effects of the Yangtze and North China cratons play the most important roles in the formation of the BTA. Crustal heterogeneity has little influence on the distribution of seismicity within the BTA. Further, the effects of subduction of the Pacific and Philippine plates may not reach the BTA area, which is different from the results of other studies.